Nodular Regenerative Hyperplasia After Liver Transplant; It’s All in the Presentation - Chen, Allen K.; Lunow-Luke, Tyler; Yamaguchi, Seiji; Praglin, Claudia; Agudelo, Eliana; Mehta, Neil; Dirks, Rachel; Braun, Hillary J.; Gardner, James M.; Roberts, John P.; Syed, Shareef M.; Roll, Garrett R. (Frontiers in Surgery, 2022)
There is a paucity of data on nodular regenerative hyperplasia after liver transplant. We aim to define the clinical disease trajectory and identify predictors of outcome for this rare diagnosis. This is a retrospective review of postulated risk factors and outcome in patients with nodular regenerative hyperplasia. Patients were classified as having a late presentation if nodular regenerative hyperplasia was diagnosed > 48 months from transplant, and symptomatic if portal hypertensive symptoms were present. Forty-nine of 3,711 (1.3%) adult recipients developed nodular regenerative hyperplasia, and mortality was 32.7% with an average follow up of 84.6 months. The MELD-Na 6 months after diagnosis did not change significantly. Patients with symptomatic portal hypertension at the time of diagnosis had a significantly higher risk of mortality (51.8%) compared to patients with liver test abnormalities alone (10.5%). 44.9% of patients had no previously postulated risk factor. Anastomotic vascular complications do not appear to be the etiology in most patients. The results suggest the vast majority of patients presenting with liver test abnormalities alone have stable disease and excellent long term survival, in contrast to the 56.3% mortality seen in patients that present more than 48 months after LT with symptomatic portal hypertension at diagnosis.